Neuroscientific and neuroanthropological perspectives in music therapy research and practice with patients with disorders of consciousness - Vogl, Julia; Heine, Astrid M.; Steinhoff, Nikolaus; Weiss, Konrad; Tucek, Gerhard (Frontiers in Neuroscience, 2015)
A growing understanding of music therapy with patients with disorders of consciousness has developed from observing behavioral changes and using these to gain new ways of experiencing this research environment and setting. Neuroscience provides further insight into the effects of music therapy; however, various studies with similar protocols show different results. The neuroanthropological approach is informed by anthropological and philosophical frameworks. It puts emphasis on a research with and not just on human beings concerning the subject/object question within a research process. It examines relational aspects and outcomes in the context of working in an interdisciplinary team. This allows a broader view of music therapy in a reflective process and leads to a careful interpretation of behavioral reactions and imaging results. This article discusses the importance of the neuroanthropological perspective on our way of obtaining knowledge and its influence on therapeutic practice. It is important to consider how knowledge is generated as it influences the results. Data from two cases will be presented to illustrate the neuroanthropological approach by comparing quantitative PET data with qualitative results of video analyses.